PERSEPSI KEADILAN: PENDORONG KARYAWAN BERPERILAKU TIDAK ETIS - Putu Irma Yunita; Kadek Trisna Dwiyanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The purpose of this study is to examine the infuence of transformational leadership to perceptional justice. Beside that it also indicated the relationship between perceptional justice to unethical behavioral. The respondence of this study was employee in hotel industries, which located in Nusa Dua area. SPSS version 20.0 was used to test the proposed hypothesis. The results showed transformational leadership can directly affect perceptional justice. However, perceptional justice had a negative effect on unethical behavioral. Discussion and limitation for future research is presented.